2013
DOI: 10.1063/1.4776227
|View full text |Cite
|
Sign up to set email alerts
|

Surface enhanced fluorescence and Raman scattering by gold nanoparticle dimers and trimers

Abstract: Dimers and trimers of gold nanoparticles were synthesized using wet chemistry method for surface enhanced fluorescence and Raman scattering. The dimers and trimers provide hot spots for enhancing the fluorescence and Raman signals, and significantly obvious enhancement is obtained from Raman signals in solution. Using finite element method, we calculate the enhancement of fluorescence and Raman signals in the experimental system. Both experimental and theoretical results show that the dimers and trimers soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 29 publications
0
40
0
Order By: Relevance
“…It is found that the fabrication of effective PEF substrate with high local EM field or "hotspots" will produce better fluorescence enhancement. Furthermore, the simultaneous enhanced Raman and fluorescence spectrum from the gold dimer and trimer nanostructure was observed recently [82]. A) The AFM image of Ag fractal-like structure, B) the model of fractal-like structure highlighted with red line circle in a), C) the simulated EM field with 532 nm (top) and 633 nm (down), and D) the PE spectra of Rh6G molecules on reference sample(curve a), and Ag fractallike structure (curve b) [72].…”
Section: Figurementioning
confidence: 99%
“…It is found that the fabrication of effective PEF substrate with high local EM field or "hotspots" will produce better fluorescence enhancement. Furthermore, the simultaneous enhanced Raman and fluorescence spectrum from the gold dimer and trimer nanostructure was observed recently [82]. A) The AFM image of Ag fractal-like structure, B) the model of fractal-like structure highlighted with red line circle in a), C) the simulated EM field with 532 nm (top) and 633 nm (down), and D) the PE spectra of Rh6G molecules on reference sample(curve a), and Ag fractallike structure (curve b) [72].…”
Section: Figurementioning
confidence: 99%
“…SERS substrates involving nanogaps have been fabricated by either bottom-up or top-down processes. For example, dimers and trimers consisting of gold NPs synthesized by a wet chemical method are shown in Figure 3a [58]. The simulated distributions of the local electric field enhancement of single particle, dimer and trimer are shown in Figure 3b-d, respectively.…”
Section: Surface-enhanced Raman Spectroscopymentioning
confidence: 99%
“…(a) spheres [17], (b) cubes [18], (c) right bipyramids [19], (d) octahedrons [20], (e) flowers [21], (f) bars [22], (g) rices [23], (h) rods [24], (i) carrots [25], and (j) wires [26]. Images of the simulated distributions of |E| 2 in logarithmic scale with 632.8 nm excitation for single gold NP, dimer, and trimer [58]. (e) SEM image of a dimer consisting of two flowerlike silver particles [63].…”
Section: Figurementioning
confidence: 99%
“…Thus, SERS is very sensitive to nanoparticle size, shape, and spatial arrangement. [2][3][4][5][6] In recent decades, great potential for application of SERS in chemical and biochemical analyses has been demonstrated. [7][8][9] There exist two main directions for development of new types of SERS substrates: one is the quest for the largest possible enhancement factor (EF) and hence for ultra-high sensitivity [10][11][12] and the other is the quest for reasonable EF of substrates with low cost fabrication for large-scale measurements.…”
Section: Introductionmentioning
confidence: 99%